The role of sleep in early language acquisition - Horvath, K (2015)
The relationship between sleep and language during infancy has not attracted a great deal of scrutiny despite its theoretical importance in the function of sleep and the practical implications to which resulting findings could contribute. With this in mind, the current thesis aims to investigate this question with a focus on word learning, generalisation of word meanings and vocabulary development. A cross-sectional design in 16 month old infants was used as one of the main approaches to test the potential effects of naps on word learning and generalisation. In both experiments, infants were randomly assigned to nap or wake conditions. After teaching two novel object-pairs to them, their initial performance was tested with an intermodal preferential looking task. An increase in target preference indicated the recognition of the auditory label—looking behaviour being monitored with an automatic eye-tracker. In the case of word learning, the same objects were shown in the test trials as in the training trials, whereas the test objects were different in colour in the generalisation experiment. In both experiments target preference increased only after a nap, while there was no change in the performance of the wake groups. These results indicate that daytime napping facilitates both the consolidation of novel words and the generalisation of novel word meanings in infancy. The relationship between sleep and vocabulary development was studied in a longitudinal questionnaire based design, in which vocabulary questionnaires and sleep diaries were employed, with a cohort of 246 children between the ages of 7 and 38 months being analysed. Sleep measures were used as predictors in a multi-level growth curve analysis of vocabulary development. The length of daytime naps was positively correlated with both expressive and receptive vocabulary growth, whereas the length of night-time sleep was negatively associated with rate of expressive vocabulary growth. To conclude, the results of the present thesis highlight the importance of daytime naps in early childhood.